Avaliação de parâmetros farmacêuticos em comprimidos matriciais empregando a técnica de Biosusceptometria AC - Oliveira, Maria Teresa de [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Oral administration is widely accepted route for drug delivery and solid dosage forms are commonly employed. The variation of absorption profiles along the human gastrointestinal tract (GIT) and the ability to target drugs by adequate dosage forms to distinct sites is the challenge in the pharmaceutical development of solid dosage forms. AC Biosusceptometry (ACB) is a technique that deserves consideration due to its features, accuracy of results and versatility. The purpose of this work was to evaluate, by employing the AC Biosusceptometer, the rate of swelling of systems matrices consisting of hydrophilic polymer (hydroxypropyl methyl cellulose) and magnetic material. Matrices tablets were evaluated in vitro to a more detailed analysis of kinetics of swelling, in addition to the study and application of mathematical models to correlate the magnetic area variation and the water uptake. All the procedures for qualitative and quantitative analysis of digital signals as well as the magnetic images processing were performed in MatLab® (Mathworks Inc.). ACB technique proved to be useful towards estimating the swelling properties of hydrophilic matrices in vitro, showing a promising capacity for further analyses involving dissolution test and in vivo studies, supporting their innovative potential pharmaceutical applications

A administração oral de fármacos é uma prática comum na terapia e as formas farmacêuticas sólidas são as mais amplamente utilizadas. A variação no perfil de absorção ao longo do trato gastrintestinal humano e a possibilidade de liberar fármacos em suas diferentes regiões representam grandes desafios para o desenvolvimento de novos produtos. A Biosusceptometria de Corrente Alternada (BAC) é uma técnica que merece destaque por suas características, precisão dos resultados obtidos e versatilidade. A proposta deste trabalho foi avaliar, por meio da BAC, a taxa de intumescimento de um sistema matricial constituído por polímero hidrofílico (hidroxipropilmetilcelulose) e material magnético. Os comprimidos matriciais foram avaliados in vitro visando uma análise mais detalhada da cinética de intumescimento, além do estudo e aplicação de modelos matemáticos para correlacionar a variação da área magnética e a quantidade de água absorvida. Todos os procedimentos de análise qualitativa e quantitativa dos sinais digitalizados, além do processamento das imagens magnéticas foram realizados em MatLab® (Mathworks Inc.). A técnica BAC se mostrou útil para estimar as propriedades de intumescimento de matrizes hidrofílicas in vitro, mostrando uma capacidade promissora para estudos posteriores que envolvam teste de dissolução ou estudos in vivo, corroborando seu potencial inovador para aplicações farmacêuticas
Keywords: Biosusceptometria de Corrente Alternada; Fisica medica